Utilizing of Geophysical Methods for Geothermal Exploration at Guru Kinayan Village, Tanah Karo Regency - Muhammad Kadri; Togi Tampubolon; Juniar Hutahaean; Nordiana Mohd Muztaza; Mohd Nawawi Mohd Nordin (Postgraduate, University of Mataram, 2025)
Guru Kinayan, located at the foothills of mount Sinabung in Karo regency, is characterized by several geothermal manifestations, highlighting the necessity of studying its geothermal potential. This research aims to assess the geothermal prospects of the area through 2-D electrical resistivity, geomagnetic surveys, and (XRD) methods. To acquire 2-D resistivity data, a Wenner Schlumberger array with a 5-meter electrode spacing was utilized, and the data were processed using Res2Dinv. Geomagnetic surveys were conducted using a PPM, with the results analyzed using Mag2dc and Surfer 13 to determine susceptibility results. The analysis of rock composition was performed using XRD. The 2-D resistivity results indicated resistivity values ranging from 1 to 1250 Ωm. Values between 1 and 20 Ωm indicated as alluvium, indicating a reservoir for geothermal, while resistivity values >1000 indicates as limestone, which indicated as a heat conductor. The magnetic residual map shows geomagnetic values (20 to 380 nT), suggesting a geothermal source, and the susceptibility values ranging (0.0013 x 10³ to 0.0088 x 10³) indicates the presence of igneous rocks, specifically andesite lava and pyroclastic rocks. The XRD results show arsenopirit and quartz in the geothermal area. Based on the integrated results, the study area has significant geothermal potential.